Making strides - Brooke, Lauren (New York : Scholastic, 2005)
Malory has earned a spot on the riding team, yet she questions whether she really belongs at Chestnut Hill. Then a new horse, wary and defensive, arrives and Malory is determined to reach him.
850
Accelerated Reader AR
Keywords: Boarding schools -- Virginia -- Juvenile fiction; Friendship -- Juvenile fiction; Horsemanship -- Juvenile fiction; Horses -- Juvenile fiction; Virginia -- Juvenile fiction